Standardization of Protocol for Agrobacteriummediated Transformation in Potato (Solanum tuberosum L.) - Molla, MMH; Nasiruddin, KM; Amin, M Al; Haque, MS; zaman, Manir uz (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted at the Laboratory of Biotechnology, Biotechnology Division, Bangladesh Agricultural Research Institute, Gazipur- 1701 during July 2007 to June 2008. An efficient and reproducible protocol for the production of transgenic potato plants was developed by inoculating internode explants of potato with Agrobacterium tumefaciens strain LBA4404 carrying a binary vector pBI121 having one reporter gene (gus) and selectable marker gene (nptII) resistant to Kanamycin. The transformation experiment was done by optimizing two important parameters names infection time and cocultivation period. Most of the explants produced shoots within 21 days on 5 mg/l Zeatin riboside (ZR) and 50 mg/l Kanamycin supplemented MS medium without introducing callus. The infected explants produced 8.27 and 6.42 shoots in Asterix and Diamant varieties, respectively within 21 days. Transgenes were confirmed by molecular analysis. DNA from well established rooted plants confirmed nptII positive through PCR analysis. The transformation rates were 28.97 and 24.37% in Asterix and Diamant, respectively. Putative transformed plants of Diamant and Asterix varieties produced roots in ½MS medium supplemented with 50/mg Cefotaxim, 50 mg/l Kanamycin and 0.5 mg/l IBA. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11220 Bangladesh J. Agril. Res. 37(2): 185-194, June 2012